2008
DOI: 10.3800/pbr.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the density and vertical distribution of nauplii, copepodites and adults of the genera Oithona and Oncaea (Copepoda) in the surface water of Toyama Bay, southern Sea of Japan

Abstract: Abstract:In this study, we examined seasonal changes in the vertical population density of each developmental stage (nauplius and copepodite) of Oithona and Oncaea species in the surface water of Toyama Bay from 1997 to 1999. Furthermore, we investigated the detailed vertical distribution (0 m, 25 m and 50 m depth) of the naupliar stages, which are regarded as an important food source for fish larvae. Major changes in the community structure of nauplii, which occurred at different sampling depths and in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Seasonal and vertical factors are several factors that can affect the abundance of Nauplius copepod within waters. Based on the previous research done by Takahashi and Uchiyama (2008), within Toyama Bay, it was found that the abundance of Naupliuscopepod genus occurred in every seasons. However, that thing is highly depend on the endurance of each species into changes within environment's condition.…”
Section: Composition and Abundance Of Phytoplankton Within Watersmentioning
confidence: 92%
“…Seasonal and vertical factors are several factors that can affect the abundance of Nauplius copepod within waters. Based on the previous research done by Takahashi and Uchiyama (2008), within Toyama Bay, it was found that the abundance of Naupliuscopepod genus occurred in every seasons. However, that thing is highly depend on the endurance of each species into changes within environment's condition.…”
Section: Composition and Abundance Of Phytoplankton Within Watersmentioning
confidence: 92%
“…These studies and some others, including the more recent ones, were focused on the distribution of so-called net zooplankton, in which meso-and macrozooplankton fractions dominate, while the issue of distribution of metazoan microzooplankton (hereinafter MM) has not been studied. MM fraction is represented primarily by copepod naupliar stages; they used to be sampled by Niskin bottles (Seregin & Popova, 2016a ;Takahashi & Uchiyama, 2008 ;Ueda, 1987), by specialized plankton nets with a mesh size of less than 60-70 µm (Uye & Sano, 1995), or by other devices (Kršinić & Grbec, 2012). In general, crustaceans could contribute up to 90 % of total MM abundance.…”
mentioning
confidence: 99%
“…MM habitat of holo-and meroplanktonic organisms in the Black Sea is constrained by the upper 50-100-m layer. Vertical distribution varies for different zooplankton species, sizes, and ontogenetic fractions (Kovalev, 1967 ;Shmeleva & Zaika, 1973 ;Takahashi & Uchiyama, 2008 ;Trudnowska et al, 2015 ;Ueda, 1987). It is influenced by season and hydrographic conditions (Takahashi & Uchiyama, 2008 ;Trudnowska et al, 2015), including the presence of thermo-, halo-, and pycnoclines (Landaeta et al, 2013 ;Lougee et al, 2002), wind mixing (Lagadeuc et al, 1997), and many other factors.…”
mentioning
confidence: 99%
“…Patterns of vertical distribution have been poorly studied on cyclopoid copepods, and only a few studies have addressed this topic on Oithona (Kosobokova 1980;Gislason 2008;Tanimura et al 2008;Takahashi and Uchiyama 2008;Saiz et al 2013) to deeper waters when they became larger, however, is not particular of Oithona, since it is widespread among neritic planktonic copepods.…”
Section: Distributionmentioning
confidence: 99%